Prefabricated Construction using Digitally Integrated Industrial Manufacturing - Giles, Harry (Enquiry The ARCC Journal for Architectural Research, 2008)
The paper describes research being carried out in relation to prefabricated high density affordablehousing under a grant from the Partnership for the Advancement of Technology in Housing(PATH) and the National Science Foundation (NSF) in the USA. The objective is to demonstratehow a new paradigm for the conceptualization and construction of buildings can be conceivedof as an entirely factory based process that creates advantages for construction through industrialsystems technology transfer. Our approach is intended to transform design methodologythrough demonstrating how alternative construction concepts, using entirely pre-manufacturedvolumetric units, can be adopted. This involves digital modeling that facilitates parametric variationsfor creating customized prefabricated products from design conceptualization through tofinal product delivery. The paper discusses key areas under investigation in relation to a manufacturingparadigm used in the automotive industry that integrates virtual prototyping and industrialmanufacturing systems. Our research explores a type of monocoque volumetric unit prefabricatedin steel, which will be pre-finished as part of a modular factory-built approach usingindustrialized methodologies that will facilitate customized manufacture of a high quality energyefficient product for affordable housing.The paper addresses the automotive industry methods of manufacture that have served increasedautomobile performance and economics through mass production for over a century. In starkcontrast, the building industry and in particular the housing industry is still a century behind. It issuggested that a move away from tradition will require an industry wide initiative, just like HenryFord led the way with mass production. By embracing the increasing sophistication and capabilitythat digital technology offers, it is shown how digital tools are implemented towards masscustomization in house design using virtual modeling in the context of a prefabricated manufacturingapproach. This includes industrialized modular sub-assembly design, where the informationon parts, assemblies and modules can be transferred to digital and robotic technology, asseen in the automotive industry, as well as achieving enhanced production efficiency through a‘supply chain’ process, which is condensed. The paper discusses how these models for manufacturecan be transferred into the housing market in order to revolutionize the cost and qualitybase of construction. Our research objective is to disseminate knowledge on this process, andshowing how through integrated transfer of automotive technologies we can implement an industrializedfabrication process for mass housing, not previously known in the building industry.